The role of attitude, subjective norms, perceived behavioral control in shaping gen z’s behavioral intentions towards gig economy participation - Ang, Jing Huang; Ng, Wan Ping; Cheaw , Mei Teng (2023)
Even though the Malaysian gig economy has been developing rapidly in recent years with the continuous influx of Gen Z, there is little research on the factors that influence the willingness of this younger generation to join the Malaysian gig economy. Therefore, on the basis of the Theory of Self-Determination, Human Capital Theory, and Theory of Planned Behaviour, this study seeks to determine the influences of Learning and Development, Work-Life Balance, Social Media Use, Leadership Qualities, Technology and Digitalization, Readiness to engage (mediator), and Commitment (moderator) on the Gen Z's Willingness to engage in the gig economy in Malaysia. Besides that, in this research, we used a higher order construct approach to classify our independent variables, such as Attitude toward gig economy (learning and development, and work-life balance), subjective norm (social media use), and Perceived behavioral control (leadership qualities, and technology and digitalization). Furthermore, in this research, we have used the questionnaire method to collect relevant data. The questionnaire we designed consists of 43 questions and a total of 405 sets of responses were gathered, followed by PLS-SEM and higher-order construct analysis using SMART PLS4 software. The analysis results show that Learning and Development, Work-Life Balance, Social Media Use, Technology and Digitalization, and Readiness to engage (mediator) have a significant relationship with Gen Z’s Willingness to engage in the gig economy in Malaysia. However, the results also found that Leadership Qualities and Commitment (moderator) did not significantly affect Gen Z's Willingness to engage in the gig economy in Malaysia. In addition, it is worth noting the mediation effect (Readiness) in our research, the results show three different situations in our model, which are complete mediation, partial mediation, and no mediation.